Using Picture Series in Teaching Writing Skill for Students of Midwife Program - Lidia Deviga; Radian Arum Ardhani (Sekolah Tinggi Agama Islam Negeri Majene, 2021)
The aim of this research was to find out the using picture series in teaching writing skill for the fourth semester students of midwifery program in STIKES Bhakti Husada Mulia Madiun. This study was done on May 2020. The subjects were 32 students of the fourth semester students of midwifery program of STIKES Bhakti Husada Mulia Madiun in the academic year 2020/2021. The method used in this research was a qualitative descriptive research design. The techniques for collecting data were observation, interview, and documentation. During the research, the researcher acted as the teacher and observer during the implementation of picture series. The findings of observation show that there is good interaction between lecturer and students. The lecturer gives the task and assignment to make the students understand the material well. The finding of interview shows that by using picture series, the students can have the ideas how to start writing recount text well. They can arrange the picture series to help them in composing the writing. By using picture series the students can improve their writing based on the criteria asked by the lecturers. The criteria of the writing are vocabulary, content, language, mechanic and organization. The finding of documentation shows that the use of picture series in teaching writing recount text make the students interested. Thus, the learning process is supported that the students are better to write from their experiences to compose recount text. Then, the use of picture series is effectively used in helping students improve their performance in writing recount text. The future researcher can conduct the use of picture series in other skill of English such as on speaking skill. It is hoped can be used as the easy media to express the students’ creativity in their speaking. Furthermore, the researcher can do this study by using the other design such as the experimental research design in teaching English writing skill.